Competitive Adsorption of Metals onto Magnetic Graphene Oxide: Comparison with Other Carbonaceous Adsorbents - Jin Hur; Jaewon Shin; Jeseung Yoo; Young-Soo Seo (The Scientific World Journal, 2015)
Competitive adsorption isotherms of Cu(II), Pb(II), and Cd(II) were examined on a magnetic graphene oxide (GO), multiwalled carbon nanotubes (MWCNTs), and powered activated carbon (PAC). A series of analyses confirmed the successful synthesis of the magnetic GO based on a simple ultrasonification method. Irrespective of the adsorbents, the adsorption was highly dependent on pH, and the adsorption was well described by the Langmuir isotherm model. The maximum adsorption capacities of the adsorbents were generally higher in the order of Pb(II) > Cu(II) > Cd(II), which is the same as the degree of the electronegativity and the hydrated radius of the metals, suggesting that the metal adsorption may be governed by an ion exchange between positively charged metals and negatively charged surfaces, as well as diffusion of metals into the surface layer. The adsorption of each metal was mostly lower for multi- versus single-metal systems. The antagonistic effects were influenced by solution pH as well as the type of metals, and they were higher in the order of the magnetic GO > MWCNT > PAC. Dissolved HS played a greater role than HS adsorbed onto the adsorbents, competing with the adsorption sites for metal complexation.